Factors Influencing Customer Satisfaction in the Food and Beverage Industry: A Case Study of Fish Grill Company - Dharmayanti, Diah; Anak Agung Ayu Puty Andrina; Nur Fathin Shaida Muhammad Nadhirin (International Business Management - Universitas Ciputra, 2024)
The food and beverage industry is a major driver of Indonesia's economic growth, yet many new ventures in this sector struggle to achieve long-term sustainability. Research shows that approximately 60% of startups fail within their first five years, often due to their inability to maintain customer satisfaction, a key factor for business survival. This study aims to investigate how four critical factors—delivery, product in hand, perceived benefits, and customer support—affect customer satisfaction at Fish Grill, a student-run venture. Grounded in the Expectation-Confirmation Theory, the research explores how these factors align with customer expectations to influence satisfaction. A quantitative method was employed, gathering data from 87 respondents through a purposive sampling method. Structural equation modeling with partial least squares was used to analyze the data. The results reveal that while delivery does not significantly impact customer satisfaction, product in hand, benefits, and customer support have a substantial positive effect. These findings suggest that in the food and beverage industry, product quality and service elements are more critical to customer satisfaction than logistical concerns. This study highlights the need for businesses like Fish Grill to focus on delivering high-quality products and excellent customer support to enhance customer satisfaction and achieve long-term success in a competitive market.